Interleukin-7 Receptor Alpha in Innate Lymphoid Cells: More Than a Marker - Sheikh, Abdalla; Abraham, Ninan (Frontiers in Immunology, 2019)
Innate lymphoid cells (ILCs) are a group of immune cells that are important for defense against pathogens, tissue repair and lymphoid organogenesis. They share similar characteristics with various subsets of helper T cells but lack specific antigen receptors. Interleukin-7 (IL-7) and thymic stromal lymphopoeitin (TSLP) are cytokines that engage the IL-7Rα and have major roles in dictating the fate of ILCs. Recent advances in the field have revealed transcriptional programs associated with ILC development and function. In this article, we will review recent studies of the role of IL-7 and TSLP in ILC development and function during infection and inflammation.